A multi-facetted visual analytics tool for exploratory analysis of human brain and function datasets (2015)
The last chapter introduced data driven research as a new way in which neuro image research will be conducted in the near future. This chapter will provide more details about data driven exploratory analyzes, visual analytics and existing tools. It will also discuss current techniques for working with neuro-image data, and how visual analytics techniques can be currently applied. This will finish setting the stage in which the thesis is developed, and make more clear the gap that will be closed by the proposed work. This is, current tools are not appropriate for conducting data driven research which make heavy use of multiple modalities of neuro-image data